MUSASHI-Mediated Expression of JMJD3, a H3K27me3 Demethylase, Is Involved in Foamy Macrophage Generation during Mycobacterial Infection. - Sahana Holla; Praveen Prakhar; Vikas Singh; Anupama Karnam; Tanushree Mukherjee; Kasturi Mahadik; Pankti Parikh; Amit Singh; R S Rajmani; Subbaraya G Ramachandra; Kithiganahalli Narayanaswamy Balaji (PLoS Pathogens)
Foamy macrophages (FM)s harbor lipid bodies that not only assist mycobacterial persistence within the granulomas but also are sites for intracellular signaling and inflammatory mediators which are essential for mycobacterial pathogenesis. However, molecular mechanisms that regulate intracellular lipid accumulation in FMs during mycobacterial infection are not clear. Here, we report for the first time that jumonji domain containing protein (JMJD)3, a demethylase of the repressive H3K27me3 mark, orchestrates the expression of M. tuberculosis H37Rv-, MDR-JAL2287-, H37Ra- and M. bovis BCG-induced genes essential for FM generation in a TLR2-dependent manner. Further, NOTCH1-responsive RNA-binding protein MUSASHI (MSI), targets a transcriptional repressor of JMJD3, Msx2-interacting nuclear target protein, to positively regulate infection-induced JMJD3 expression, FM generation and M2 phenotype. Investigations in in vivo murine models further substantiated these observations. Together, our study has attributed novel roles for JMJD3 and its regulators during mycobacterial infection that assist FM generation and fine-tune associated host immunity.